Effects of platelet rich plasma on fascial healing in rats with fecal peritonitis - Girgin, Mustafa; Binnetoglu, Kenan; Duman, Kazim; Kanat, Burhan Hakan; Cetinkaya, Ziya; Ayten, Refik; Timurkaan, Necati (Acta Cirurgica Brasileira, 2016)
PURPOSE: To evaluate the effects of platelet rich plasma (PRP) on the healing of fascia wherein peritonitis has been created. METHODS: Twenty eight Wistar Albino rats were divided into four groups. Only a primary fascial repair following laparotomy was performed on Group 1, a primary fascial repair performed and PRP treatment applied following laparotomy on Group 2, and a fecal peritonitis created following laparotomy and a primary fascial repair carried out on Group 3. A fecal peritonitis was created following laparotomy and primary fascial repair and PRP treatment on the fascia was carried out on Group 4. RESULTS: TNF-alpha was found to be significantly lower in the control group (Group 1). It was detected at the highest level in the group in which fecal peritonitis was created and PRP applied (Group 4). TGF-beta was determined as being significantly higher only in Group 4. Histopathologically, the differences between the groups in terms of cell infiltration and collagen deposition were not found to be significant. CONCLUSION: When platelet rich plasma was given histologically and biochemicaly as wound healing parameters cellular infiltration, collagen accumulation, and tissue hydroxyiproline levels were not increased but neovascularization, fibroblast activation and TNF Alfa levels were increased and PRP accelerated wound healing.
Keywords: Platelet-Rich Plasma; Peritonitis; Wound Healing; Rats